2020
DOI: 10.1016/j.jaad.2019.12.038
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cumulative clinical benefits of biologics for the treatment of psoriasis over 16 weeks: Results from a network meta-analysis

Abstract: Background: Cumulative clinical improvement and speed of improvement are important to psoriasis patients.Objective: Compare cumulative benefits of biologics over 12 to 16 weeks in the treatment of moderate to severe psoriasis.Methods: A systematic literature review identified phase III trial data on Psoriasis Area and Severity Index (PASI) responses for biologics during 12 and 16 weeks of treatment. Cumulative clinical benefit, measured by the area under the curve for PASI $75% improvement (PASI 75), $90% impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
66
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 45 publications
2
66
0
3
Order By: Relevance
“…The remaining eighteen provided details of conflicts of interests and the funding received. Seven NMAs [17,23,24,26,[33][34][35] were funded by public grants (such as from the Institute for Clinical and Economic Review [24] or the Cochrane Collaboration [33,34]) and eleven by drug manufacturers [20,[30][31][32][36][37][38][39][40][41][42].…”
Section: Source Of Funding and Conflicts Of Interestmentioning
confidence: 99%
“…The remaining eighteen provided details of conflicts of interests and the funding received. Seven NMAs [17,23,24,26,[33][34][35] were funded by public grants (such as from the Institute for Clinical and Economic Review [24] or the Cochrane Collaboration [33,34]) and eleven by drug manufacturers [20,[30][31][32][36][37][38][39][40][41][42].…”
Section: Source Of Funding and Conflicts Of Interestmentioning
confidence: 99%
“…To the Editor: Limited data are available to guide use of biologics for moderate to severe plaque psoriasis in the current coronavirus disease 2019 (COVID-19) health care landscape. 1 , 2 We aimed to further understand the rate of patient-driven biologic discontinuation in moderate to severe psoriasis because of concerns regarding COVID-19 complications. Furthermore, our goal was to add to the limited but increasing body of literature on whether biologic use should be considered a risk factor for greater susceptibility to COVID-19.…”
mentioning
confidence: 99%
“…Vismodegib has unusual pharmacokinetics; it is highly bound to plasma proteins, particularly alpha-1-acid glycoprotein, and biological activity does not increase with dose. 5 Sonidegib has a more conventional dose-response relationship. For this reason the two registration studies had different deigns.…”
Section: Hedgehog Pathway Inhibitors Come Of Agementioning
confidence: 99%
“…[1][2][3][4] Rapidity of clearance has been the focus of two recent network metaanalyses (NMAs) and a systematic review, which conclude that ixekizumab and brodalumab, two agents that inhibit interleukin (IL)-17A, are the fastest-acting treatments when compared with other biologics and conventional systemic agents. [5][6][7] Similarly, a study examining the time-effectiveness of simulated induction sequences revealed that initiating treatment with ixekizumab resulted in the shortest time to achieving a clinically significant reduction in dermatology life quality index (DLQI) for 25% of patients (1Á4 weeks). 8 However, to place these findings in context, a recent update of a Cochrane NMA of overall clinical effectiveness, rather than speed of action, in achieving ≥ 90% reduction in their Psoriasis Area and Severity Index score (PASI 90) in the induction phase (8-24 weeks), established that infliximab, all the IL-17 inhibitors (ixekizumab, secukinumab, bimekixumab and brodalumab) and IL-23 inhibitors (risankizumab and guselkumab, but not tildrakizumab) were similar in efficacy.…”
mentioning
confidence: 99%